Comprehensive assessment of the environmental and employment impacts of international trade from the perspective of global value chains - Bai, Shukuan; Zhang, Boya; Ning, Yadong (Frontiers in Environmental Science, 2023)
A comprehensive assessment of the environmental and employment impacts of international trade is essential for coordinating sustainable development between the economy, environment, and society. International trade is an important driving force for global economic growth. However, the environmental and social impacts of trade under global value chains (GVCs) have not yet been comprehensively characterized. This study aims to estimate the impacts of international trade from 2000¬–2014 on carbon emissions and employment using the gross export decomposition method, incorporating a counterfactual method based on the multi-region input–output model. We found that (1) at the global level, international trade has been conducive to carbon emission reductions since 2003 and played a role in increasing employment throughout the study period; however, the impacts of GVC-related trade have been mixed, generating global emissions savings, but leading to job losses. This implies that there is a trade-off between carbon emission reduction through GVC embedding and employment creation. (2) At the national level, a country’s participation in international trade benefits the environment, employment, or both. In this sense, international trade is no longer a zero-sum game; rather, it is likely to be a positive-sum game for all participants regarding environmental benefits and job creation. (3) In bilateral trade, developed and developing economies have positive and negative impacts, meaning that they should take joint actions to balance environment–employment–trade growth. These findings are useful for determining the responsibilities of different countries toward climate change and achieving sustainable development of the economy, society, and environment.